ANALISIS ANALISIS HUBUNGAN ANTARA SEDENTARY LIFESTYLE DENGAN KEJADIAN OBESITAS PADA USIA SEKOLAH DASAR KELAS 4-6 (Studi di Kota Salatiga) - Yemema Victory Sandi Saputra; Henry Setyawan; M. Arie Wuryanto; Ari Udiyono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Background: Obesity is the form of abnormality or the accumulation of fat that can impact on health. For children and adolescent aged 5-18 years old, said to be obese if BMI (Body Mass Index) according to age more than 2 according to Z score. Obesity occurs if the intake of energy is greater than energy used. In Indonesia, the prevalence of obesity chilren aged 5-12 years old was 8,8%, 7,9% for Central Java, and 5,1% for Salatiga. Purpose: The purpose of this study was to analyze the risk factors that associated to obesity children in elementary school grade 4-6. Method: The method was quantitative method and the type of the research was observational analytical with a cross sectional approach. The population of this study was the students of elementary school grade 4-6 in Salatiga. The reached population was the students of Marsudirini 77 Elementary School grade 4-6 then the sample was taken as many as 60 resopondents using random sampling system. Result: The result indicated that as many as 22 (36,7%) respondents suffered from obesity with 13 (59,1%) respondents were male and 9 (40,9%) respondents were female. Conclusion: For bivariate analytical used Chi-square correlation test showed a correlation between familial (p=0,038; POR=3,6) dan sedentary lifestyle (p=0,022; POR=4,6) with obesity children in elementary school grade 4-6 and there was no correlation between physical activity (p=0,543) and energy intake (p=0,436) with obesity children in elementary school grade 4-6.